Web 2.0 applications in top Chinese university libraries - Han, Zhiping; Liu, Yan Quan (Library Hi Tech, 2010)
Purpose - This paper aims to explore the status and construction pattern of Web 2.0 technologies employed in top Chinese university libraries, their functionalities and features. Design/methodology/approach - A combination of online survey and content analysis methodology is applied to a sample of 38 top Chinese university libraries' web sites. The Web 2.0 tools are categorized by generally accepted standards with some adjustment for library practices. Data were collected by accessing these university library web sites on two separate occasions during the period of February 10-20, 2009 by utilizing a checklist of 52 questions. Findings - More than two-thirds of the 38 top Chinese university libraries apply one or more kinds of Web 2.0 tools through the basic functions of their web sites. Among six types of tools, Catalog 2.0 and RSS are the most common, while IM, Blog, SNS and Wiki are less frequent. Research limitations/implications - Internal applications that are not publicly accessible contain hidden information that may not be gathered through content analysis since these links usually cannot be found on library web sites. It is difficult to get exact information as to the applications of Web 2.0 in these libraries without an interview method in combination to observation. Originality/value - This study provides an overall picture of Web 2.0 tools developed in top Chinese university libraries, allowing for future evaluation and planning. The implementation of Web 2.0 applications and their constructing pattern is not only indicative of the development of the Chinese digital libraries, but also to their development of digital libraries in the world at large.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/148-213-665-014-156 tex.unique-id: [object Object]
Keywords: China; Digital libraries; University libraries; Worldwide web; dept.ils; peer-reviewed